Human Capital Management Policy Effect on Employee Performance - Maharani, Anita; Juliansyah, Didi; Sanjaya, Roni Putra (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2020)
This study aims to look at the effect of the application of human capital management in terms of practices such as recruitment and selection, placement, training and development, performance appraisal, compensation and benefits, and the relationship between employees and employee performance. This research approach is quantitative, all data obtained will be obtained by taking a number of procedures, the validity test, reliability and hypothesis testing using SmartPLS SEM in finding out the relationship between HCM practices and employee performance, the results of the study show the relationship and influence of the human capital management to employee performance.